Predicting the persistency and permanency as well as relations between two stages DNA splicing languages using C# - Mudaber, Mohammad Hassan; Yuhani, Yusof; Mohd Sham, Mohamad (Universiti Teknologi Malaysia, 2014)
Splicing system is the a system of studying the relation between mathematics and biology which was invented by Head in 1987.